In vitro maturation of Brycon henni eggs (Pisces: Characidae) with two hormonal preparations - Montoya Páez, Juan David (2018)
The ‘sabaleta’ (Brycon henni) is a species of commercial interest in Colombia. One of the main barriers to the conservation processes of this species is the temporal asynchrony between the reproductive cycles of females and males, which could be solved using biotechnological processes. The aim of this investigation was to evaluate the in vitro maturation of ‘sabaleta’eggs (Brycon henni) using two hormonal preparations. A total of 1200 eggs were subjected to in vitro maturation in the presence of carp pituitary extract (EPC), salmon gonadotropin-releasing hormone (sGnRHa) and a control without hormonal stimulation. The eggs were incubated for 2 hours at 25 °C in constant orbital shaking and 80% O2. The in vitro maturation of the eggs was evaluated by classifying the position of the nucleus in four categories: migratory, central, atretic and peripheral. Higher maturation advancement were obtained due to the presence of migratory nucleus (p<0.05) for EPC (46.0 ± 8.4%) and sGnRHa (40.0 ± 13.3%), compared to the control (24.0 ± 9.6%). It is concluded that the use of EPC and sGnRHa hormonal preparations during in vitro maturation promotes the advancement of maturation of ‘sabaleta’ eggs (Brycon henni).